2011
DOI: 10.1111/j.1748-1716.2011.02340.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane cycling after the excess retrieval mode of rapid endocytosis in mouse chromaffin cells

Abstract: Excess retrieval is not associated with the cycling of releasable vesicles, but it is related to the formation of non-releasable endosomes. This process is activated by a concerted contribution of Ca(2+) entry through L-channels and Ca(2+) release from endoplasmic reticulum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Fitting of the colocalization data to a mono-exponential function ( y = y 0 + Ae − x / t ) ( Fig. 2b ) 39 revealed that the internalization half time ( t 1/2 ) of Megalin was 1.2 min, with a 95% confidence interval (CI 95 ) of 0.8−1.8 min. The fraction of 647-MαHA that co-localized with 488-GαM plateaued at 19% (CI 95 =14−22%), consistent with a 19% PM/ 81% intracellular steady-state distribution of Megalin, very similar to the 18% PM/80% total ratio observed in surface biotinylation assays in polarized MDCK cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fitting of the colocalization data to a mono-exponential function ( y = y 0 + Ae − x / t ) ( Fig. 2b ) 39 revealed that the internalization half time ( t 1/2 ) of Megalin was 1.2 min, with a 95% confidence interval (CI 95 ) of 0.8−1.8 min. The fraction of 647-MαHA that co-localized with 488-GαM plateaued at 19% (CI 95 =14−22%), consistent with a 19% PM/ 81% intracellular steady-state distribution of Megalin, very similar to the 18% PM/80% total ratio observed in surface biotinylation assays in polarized MDCK cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Adrenal glands from two 13–18 days old female/male 129/sv mice were used in each culture. Chromaffin cells were isolated and cultured following the procedures described by Perez Bay et al (2012) . Briefly, mechanically isolated adrenal medullas were digested for 25 min in Hanks with papain (0.5–1 mg/ml) at 37°C, and disrupted with a yellow tip in Dulbecco’s modified Eagle’s medium low glucose, supplemented with 5% fetal calf serum, 5 μl/ml penicillin/estreptomicina, 1.3 μl/ml gentamicin, 1 mg/ml bovine seroalbumin, and 10 μM citosine-1-β- D -arabinofuranoside.…”
Section: Methodsmentioning
confidence: 99%
“…Both recycling and degradation pathways coexist and their proportion may depend on cell secretory activity. The recycling pathway leading to releasable granules is more predominant upon mild stimulation whereas above a certain threshold of membrane incorporation during intense exocytotic activity, the occurrence of bulk endocytosis will lead to the degradation of the internalized membrane (54, 55). Altogether, these data do not provide any information concerning the immediate fate of internalized granule membrane.…”
Section: Endocytic Pathwaymentioning
confidence: 99%